Pengaruh Integrasi Internal terhadap Kinerja Perusahaan Plywood di Propinsi Riau - Djamin, Djanimar (Universitas Brawijaya, Indonesia, 2008)
The research aims to analyze the relationship between internal integration and company's performance. A semi survey research method was used. Plywood manufacturers located in Riau Province were taken as samples. The study is a verificative and descriptive in nature. All managers involved in production supply chain was the population of this research. They consisted of 142 people. Proportional Stratified Random Sampling was used. 14 companies were involved, while 105 people became respondents. Data were collected through interviews and questionairre. Data were analyzed with the help of software SPSS for windows. Multiple linear regression was used in order to test hypothesis proposed. The results showed that internal integration was proved to have significant effects on the increase of company's performance.